PERAN MANAJEMEN PENGETAHUAN DAN TEKNOLOGI DALAM PENGEMBANGAN PARA PEMIMPIN DI ERA DIGITAL - Aprilia, Sabrina Dwi; Sugiharti, Tanti (Proceeding National Conference Business, Management, and Accounting (NCBMA), 2024)
Implementing knowledge management within an organization is to transforming the organizational culture. Knowledge management implementation encourages the development of a knowledge-sharing culture and learning habits that involve all personnel in the organization. This is why the initial stages of knowledge management implementation are often the most challenging for organizations, as there may be resistance to change or a lack of interest in knowledge management implementation. This is where the crucial role of organizational leaders comes into play in leading knowledge management implementation. Leaders are directly responsible for guiding this change. Certainly, tangible actions from leaders are essential to motivate organizational members to actively engage in knowledge management implementation and demonstrate their commitment through concrete actions. This article constitutes a library study and identifies that knowledge management and technology play a crucial role in enhancing organizational leadership capacity.